Microwave-assisted fast and efficient dissolution of silkworm silk for constructing fibroin-based biomaterials. (2nd November 2018) - Li, Shouchuan; Chen, Chunyu; Zhang, Di; Zhang, Xiaozhong; Sun, Baochang; Lv, Shanshan
Highlights: A microwave-assisted method for efficient regeneration of silkworm silk fibroin. Significantly shortened dissolution time via the microwave-assisted method. Significant energy saving achieved by the microwave-assisted method. Abstract: A microwave-assisted method was developed for extraction of water-soluble fibroin from silkworm silk. In order to explore enhancing effect of microwave, dissolution profiles of silk fibroin were monitored by protein concentration measurements, showing a faster extraction rate of the microwave-assisted method compared to the conventional methods. Meanwhile, characterization of the resultant silk fibroin regenerated by the microwave-assisted method indicated similarity to that by the conventional methods in that they exhibited similar molecular weight ranges, secondary structures and gelation capabilities. In contrast to traditional microwave-assisted methods, this study employed a laboratory microwave reactor equipped with a feedback temperature control system, which enabled easy control and maintenance of certain reaction temperature and temperature distribution. In this way, the present study, to an extent, resolved possible concerns that uncontrollable extreme high temperature under microwave would cause degradation of the silk fibroin chain. This new microwave-assisted method has demonstrated its advantages of significant reduction in time-consuming and energy cost, and thus stands for a promising economical and efficient method for regeneration of silkworm silk fibroin.